Pengaruh Kompensasi Dan kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Winsen Kencana Perkasa - Toni Toni; Mauli Siagian (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study aims to determine the effect of (X1) compensation and (X2) job satisfaction on (Y) employee performance at PT Winsen Kencana Perkasa by using this 130 response saturation sampling technique. The data collection method used a questionnaire. This study uses multiple regression test results showing that (X1) compensation and (X2) job satisfaction have a positive effect on (Y) employee performance based on regression results and with the value of R Square. Based on statistical data, the indicators in this study are valid and reliable variables. Hypothesis testing using the t test shows that (X1) compensation and (X2) job satisfaction are proven to have a significant effect on (Y) employee performance. Then through the F test it can be seen that the variable (X1) compensation and (X2) job satisfaction simultaneously must have an effect on employee performance variables with F count greater than F table